2024
DOI: 10.3390/ma17030560
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Processing, Properties, and Applications of Closed-Cell Aluminum Foams: A Review

Wensheng Fu,
Yanxiang Li

Abstract: Closed-cell aluminum foams have many excellent properties, such as low density, high specific strength, great energy absorption, good sound absorption, electromagnetic shielding, heat and flame insulation, etc. As a new kind of material, closed-cell aluminum foams have been used in lightweight structures, traffic collision protections, sound absorption walls, building decorations, and many other places. In this paper, the recent progress of closed-cell aluminum foams, on fabrication techniques, including the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 170 publications
0
1
0
Order By: Relevance
“…In [30], in fig. 20, data from six different authors on the dependence of σp on the porosity of an aluminum foam were shown.…”
Section: Pressionmentioning
confidence: 99%
“…In [30], in fig. 20, data from six different authors on the dependence of σp on the porosity of an aluminum foam were shown.…”
Section: Pressionmentioning
confidence: 99%